Aquisição de dados em um veículo de competição F-SAE - Serralvo Neto, R. (2010)
This work has the internet to present the preparation and instrumentation of a student competition racing vehicle FSAE, developed by Fei University students, for the data acquisition using AIM system. The main focus of this work is to explore the software potential to present thousands of data obtained by various sensors installed on the racing vehicles RS3 and RS4. This data can be used to input a lot of information con computational tools for example: MSC ADAMS, NASTRAN, ANSYS, etc. Data analysis techniques will be shown , aiming the differences visualization and the potential gains that the team could have, depending on the set-up or component choice. With the data acquisition system, it is possible to achieve better results in a shorter time and less cost. The different types of driving styles will be discussed on this work. Every single possibility to improve the final vehicle performance should be explored, with all the information registered on the data acquisition system.